Comparing the dimensions of banking business model in Iran with universal banking - sadegh sepandarand; Mahdi Haghighi Kaffash; Vahid Nasehifar; Vahid khasheie (‫مدیریت بازرگانی, 2016)
Considering the change in structure and regulations governing banks during last two decades, rivalry among banks have been rapidly increased, and quality of services has been recognized as an important indicator of organization, banks and financial institutions performance. Meanwhile several financial institutions have tried to design a system to improve quality of their performance in long run and most of the banks are formulating or implementing a comprehensive strategy in financial corporation level. A comprehensive and global system based on stockholder's performance and market risk. In interviews with 14 experts in Iran banking industry and universal banking field we have compared the dimensions of banking business model in Iran and universal banking. Thematic analysis shows that banking model in Iran and universal banking are different in nine dimensions of their respective business models.